Design and application of a device for collecting body fluid samples (一种体液标本留取装置的设计与应用) - QIAN Xiaoge (茜晓格); YANG Hui (杨慧); SUN Xiumei (孙秀梅) (Journal of International Translational Medicine Limited, 2024)
This study introduces a new device for collecting body fluid samples, which can achieve the whole process of closed collection, avoid contamination of specimens, and effectively reduce occupational exposure risk. The amount of specimens collected is easy to control and can be repeatedly retained, which is conducive to improving the efficiency of clinical diagnosis and nursing. (正确留取体液标本对确保检验结果的准确性至关重要。本研究介绍了一种新型体液标本留取装置, 该装置能够实现全程密闭式采集, 避免污染标本, 有效降低职业暴露风险; 且标本采集量易于控制, 可重复留取, 有利于提高临床诊疗护理工作效率。)